2011
DOI: 10.1007/s10641-011-9926-8
|View full text |Cite
|
Sign up to set email alerts
|

PCD Risk 1: A tool for assessing and reducing ecological risks of hatchery operations in freshwater

Abstract: PCD RISK 1 is a flexible computer model designed to assist in assessment and reduction of ecological risks to natural origin fish from hatchery fish releases. PCD RISK 1 simulates predation, competition, and disease impacts on naturally produced salmonids caused by hatchery smolts in fresh water as they move downstream or residualize after release. Individual-based, the model relies upon user specified inputs of up to 45 variables, such as number and size of hatchery and wild fish, and water temperature. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Indeed, long‐term monitoring of spring Chinook Salmon populations in the Wenatchee River watershed indicated density‐dependent growth and survival of naturally produced spring Chinook Salmon (Hillman et al 2019). However, modeling using the PCD (predation–competition–disease) Risk 1 model in the Wenatchee River subbasin (Pearsons and Busack 2012) suggested that ecological risks associated with the White River program were within acceptable limits for the nontarget taxa that were evaluated (Pearsons et al 2012; Mackey et al 2014). In contrast to the findings for the Yakima River, where large numbers of hatchery‐origin minijacks were observed below the spawning grounds and few were found on the spawning grounds (Pearsons et al 2009), we detected a large number of minijacks on the spawning grounds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, long‐term monitoring of spring Chinook Salmon populations in the Wenatchee River watershed indicated density‐dependent growth and survival of naturally produced spring Chinook Salmon (Hillman et al 2019). However, modeling using the PCD (predation–competition–disease) Risk 1 model in the Wenatchee River subbasin (Pearsons and Busack 2012) suggested that ecological risks associated with the White River program were within acceptable limits for the nontarget taxa that were evaluated (Pearsons et al 2012; Mackey et al 2014). In contrast to the findings for the Yakima River, where large numbers of hatchery‐origin minijacks were observed below the spawning grounds and few were found on the spawning grounds (Pearsons et al 2009), we detected a large number of minijacks on the spawning grounds.…”
Section: Discussionmentioning
confidence: 99%